Urgensi Produk Hukum Desa Sebagai Dasar Penyelenggaraan Pemerintahan Desa - Muh Alfian Fallahiyan; Rahmadani; Iskandar Sukmana (LPPI UMN AL WASHLIYAH, 2026)
This community service activity aimed to enhance the understanding of village officials and BPD members regarding the urgency of village legal products as the foundation of village governance and to strengthen institutional capacity in drafting village regulations. The activity involved village officials, BPD members, and community leaders and was conducted through legal education, Focus Group Discussion (FGD), and legal consultation methods. The results indicated that prior to the activity, most participants had limited understanding of the hierarchy and formation procedures of village legal products. After the implementation, participants demonstrated improved understanding of the urgency of village legal products and institutional roles in their implementation. This activity contributes to strengthening village institutional capacity and supports the realization of participatory and accountable village governance.